Pore-scale study of fluids flow and fluid-fluid interactions during near-miscible CO2 EOR and storage in oil reservoirs. Issue 1 (1st December 2019) - Seyyedi, Mojtaba; Sohrabi, Mehran
Summary: CO2 injection in oil reservoirs has been widely accepted as an effective EOR and CO2 storage technique. While oil recovery and CO2 storage potential of this technique at the core scale has been widely studied, complex fluids flow and fluid-fluid interactions at the pore-scale during nearmiscible CO2 injection require further study. For this aim, a unique high-pressure and high-temperature microfluidic system was used to conduct experiments at 2, 500 psi and 40°C using live reservoir crude oil. According to results, during tertiary CO2 injection, due to the positive value of spreading coefficient, CO2 flowed only inside the oil and oil spread over CO2 and prevented CO2 contact the water. Due to unfavourable mobility ratios and permeability heterogeneities, displacement during tertiary CO2 flooding was unstable and viscous fingering occurred which led to an early breakthrough of CO2 and bypassing of a large amount of oil. However, after CO2 breakthrough, CO2 gradually started to flow inside the bypassed oil zones in the transverse/backward directions which is a characteristic of capillary fingering. Due to the gradual diffusion of CO2 into the bypassed oil, IFT between oil and CO2 decreased which led to a reduction of threshold capillary pressure, thus CO2 (non-wetting phase) entered the bypassed oil-filled pores. As a result of this unique mechanism, oil recovery after CO2 breakthrough significantly increased and almost all the bypassed oil was produced. The extent of this oil recovery mechanism depends on the extent of CO2 -oil IFT reduction which depends on injection pressure. During CO2 flow in pores, CO2 displaced the water through multiple displacement mechanism. CO2 displaced the oil in the open-end pores thorough bulk flow, and the spreading oil layers were gradually produced by film flow. Uniquely, CO2 produced the oil in dead-end pores through a mix of bulk flow and film flow. The outcomes of this study provide an in-depth understanding of fluids flow and fluid-fluid interactions during near-miscible CO2 EOR-storage.